Pengaruh Moderasi Opini Audit terhadap Persistensi Laba - Benedicta Anggit Sekartaji; Ghizella Nada Elvina; Titin Pranoto; Yang Elvi Adelina (Studi Akuntansi dan Keuangan Indonesia, 2020)
This research aims to analyze the effect of last year earnings to current earnings which moderated by audit opinion from listed companies on Indonesia Stock Exchange from 2011-2017. Total sample of this research are from 288 companies, which consist of 2.016 samples, including all of industries except financial industries chosen by purposive sampling method. Model of data analysis for this research uses Driscoll-Kraay method in pooled least square model.The result of this research found that last year earnings have positive significant effect on current earnings. The effect was describe as earnings persistence. Moreover, this research also indicates the effect of last year earnings on current earnings is moderated by audit opinion. Which modified audit opinion is proven to weakens the earnings persistence. The sensitivity test also showed that qualified and disclaimer opinion are proven to weaken earnings persistence. This research uses only one model to measure the earnings persistence. The result on qualified and disclaimer audit opinion is not representative due to less total sample on both audit opinion. Researchers expecting that this research can give a new comprehension for management about earnings persistence and audit opinion, and also can help investor for taking a decision on investment. Keywords: Earnings Quality, Audit Opinion, Earnings Persistence https://doi.org/10.21632/saki.2.2.177-202